Uso do índice de reflectância NDVI na estimativa de características fenotípicas em quatro genótipos de feijão-comum - Santana, Arthur Vieira de (2015)
The common bean (Phaseolus vulgaris L.) is a main component of Brazilian population diet, and is among of the four most economically important annual crop in Brazil. Given the social and economic importance of the bean, the development of methods to enable the condition monitoring of plants is necessary. In this context arises the remote sensing, in which the interaction of the electromagnetic spectrum with vegetables results in absorption, reflection or transmission of energy. For remote sensing the reflected energy is the main object of study. The energy after interaction is reflected in different wavelengths, which combinations give rise to the vegetation index. There are several vegetation index obtained from remote sensing, among them one of the most used is the normalized difference vegetation index (NDVI). Remote sensing has become an important tool for researchers, mainly to government action, since it identifies and monitor crops, harvest time, make projections and supervise the environment. According to the above, the objective of this study was to evaluate the efficiency of the NDVI vegetation index in determining leaf area index, total dry biomass, stem dry matter and leaf dry matter of four common bean genotypes. The experiment was conducted in the field, at the National Rice and Beans Research Center of Brazilian Agricultural Research Corporation (EMBRAPA), located in Santo Antônio of Goiás. Was used the randomized block design in a 24 factorial design, two sowing dates and four genotypes, in four replications. Sowing dates were 05.17.2013 and 07.03.2013. The genotypes used were: BRS Pérola, Bat 477, BRS Pontal and BRS Agreste. Obtaining the NDVI occurred with radiometric sensor field. The leaf area index (LAI), total dry matter (TDM), stem dry matter (SDM) and leaf dry matter (LDM) were determined with the collection of five plants per meter, which separated the stems and leaves. The leaf area was measured with a photoelectric integrator. According to the results it was observed that at 40 days after emergence NDVI were saturated for two sowing dates. The LAI, the TDM, SDM and LDM for each genotype, were well estimated from NDVI. The root mean square error (RMSE) and the mean absolute error (MAE) were more suitable for assessing the quality of the models within the same biophysical parameters. Despite the genotype and sowing date have affected the adjustment of models, it is possible to estimate the biophysical characteristics from bean with a linear generic model. Among the culture biophysical indicators the SDM was the best parameter estimated overall model and the LDM was the worst.